(untitled) (TAMADDUN NURI JURNALI, 2024)
This article examines the role and importance of didactic materials in teaching Latin. It explores methods to enhance learning efficiency through didactic resources and analyzes their application across various formats. The paper presents specific examples of how modern technology, visual aids, and supplementary materials improve Latin language instruction.